PERSONAL LAWS IN INDIA FROM A MEN’S RIGHT PRESPECTIVE - 1. Dr. Karan Singh Gaur, 2. Garima Yadav, 3. Priyanka Arya (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
India’s legal landscape is a tapestry woven from diverse cultural threads, with personal laws serving as foundational principles governing various familial and marital matters. These laws, deeply entrenched in religious traditions and societal customs, have undergone a complex evolution over centuries, shaped by historical, colonial, and socio-political influences. In recent decades, the discourse surrounding gender equality and women’s rights has gained considerable momentum, leading to significant legal reforms aimed at rectifying historical injustices and advancing women’s empowerment. However, amidst this progressive shift, there remains a notable dearth of attention paid to the rights and experiences of men within the ambit of personal laws. By exploring the historical context and evolution of personal laws, analyzing the intersectionality of gender with other social identities, and advocating for policy recommendations and reform measures, this study seeks to contribute to the ongoing discourse on gender equality and justice in India. Moving forward, it is imperative to foster greater dialogue and collaboration among stakeholders to build a legal system that upholds the rights and dignity of all individuals, irrespective of gender. The primary aim of this study is to critically analyze the various facets of personal laws in India and assess their implications for men’s rights. Despite the constitutional guarantee of equality before the law irrespective of gender, the practical application of personal laws often reflects entrenched gender biases and stereotypes, which can have adverse effects on men’s rights.